A geologically supervised spectral analysis of 121 globally distributed impact craters as a tool for identifying vertical and horizontal heterogeneities in the composition of the shallow crust of Mercury. (1st November 2016) - D'Incecco, Piero; Helbert, Jörn; D'Amore, Mario; Ferrari, Sabrina; Head, James W.; Maturilli, Alessandro; Hiesinger, Harald
Abstract: In the present work, we expose procedures and results from a global scale geologically supervised spectral analysis of 121 impact craters on Mercury, selected on the basis of specific morphologic criteria. Using the capabilities of DFTs developed by PEL researchers at DLR, we combined MASCS spectra from the DLR database with MDIS high-resolution images. We use impact structures as a window for identifying vertical and horizontal compositional heterogeneities in the shallow crust of Mercury. Using specific GIS queries on a global scale, we defined five morphologic classes of units for each of the 121 impact craters, moving outward from the central peak to deposits at ten radii distance from the crater rim. We also used an external reference area as a term of comparison to represent intercrater plains. We then retrieved all the available MASCS spectra contained within each of those units. We analyzed the spectral slopes in the 350–450 nm and 450–650 nm ranges and reflectances in the 700–750 nm range using two different approaches, the first one being more conservative than the second one. The results indicate that the central peaks class is spectrally the most heterogeneous compared to all the other defined classes. As we move outward from the central peaks to external deposits, the other morphologic classes tend to get more and more spectrally and compositionally homogenous and more similar to intercrater plains. We identified a dependency of the spectral slopes from latitude. The spectral slopes of the analyzed deposits tend to decrease at increasing latitudes. This result might indicate the presence of a global N-S dichotomy in the composition of the shallow crust of Mercury. The detailed analysis of three impact craters with distinctive spectral characteristics revealed as well the occurrence of short-range horizontal heterogeneities in the composition of the shallow crust of Mercury. Highlights: We looked for the presence of vertical and horizontal variations in the crustal composition of Mercury. We selected 121 globally distributed fresh impact craters. We defined geologic units for the 121 selected craters. We retrieved MASCS normalized spectra covering the units defined for the 121 impact craters. The results confirm the presence of vertical and horizontal heterogeneities in the shallow crust of Mercury.